1988
DOI: 10.1021/ie00081a022
|View full text |Cite
|
Sign up to set email alerts
|

A systematic method for the study of the rate-controlling mechanisms in liquid membrane permeation processes. Extraction of zinc by bis(2-ethylhexyl)phosphoric acid

Abstract: A mathematical model of a process in which an exothermic, second-order reaction takes place in a falling film reactor was developed. This model is applicable to a process in which any step, liquid mass transfer, reaction rate, or gas mass transfer, can affect the process rate. The model includes a turbulent diffusivity term for the liquid mass transfer, valid through the entire liquid film. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…More recently, stirred cell contactors have been used for the evaluation of the kinetics of metal extraction by liquid ion exchangers. Such examples include extraction of copper by benzoylacetone (Kondo et al, 1978), extraction of cobalt, copper, and nickel by bis(2-ethylhexyl) phosphoric acid (Komasawa and Otake, 1983; Brisk and McManamey, 1969), extraction of zinc by bis(2-ethylhexyl) phosphoric acid (Huang and Juang, 1986; Uribe et al, 1988). This apparatus has the advantage of a well-defined interfacial area for reaction.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, stirred cell contactors have been used for the evaluation of the kinetics of metal extraction by liquid ion exchangers. Such examples include extraction of copper by benzoylacetone (Kondo et al, 1978), extraction of cobalt, copper, and nickel by bis(2-ethylhexyl) phosphoric acid (Komasawa and Otake, 1983; Brisk and McManamey, 1969), extraction of zinc by bis(2-ethylhexyl) phosphoric acid (Huang and Juang, 1986; Uribe et al, 1988). This apparatus has the advantage of a well-defined interfacial area for reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The use of organophosphorous compound in the liquidliquid extraction of transition metals has been steadily increasing because of their excellent selectivity nature in forming complexes under different conditions. Typical extractants are di(2ethylhexyl)-phosphonic acid (D2EHPA) [5,[7][8][9] and bis (2,4,4-trimethylpentyl)-phosphinic acid (Cyanex 272) [10]. The extraction mechanism has been analyzed but relatively few studies with phosphonic acid monoester (PC-88A) have been reported [11].…”
Section: Introductionmentioning
confidence: 99%
“…The end of the 80s registers the appearance of one of the largest membrane groups in Spain, that led by Inmaculada Ortiz, initially at the University of the Basque Country, and since the early 90s, at the University of Cantabria. Being part of a purely Chemical Engineering department, Prof. Ortiz published her first paper on liquid membranes in 1988 in Industrial and Engineering Chemistry Research [43]. This group of chemical engineers introduced a strong focus on the design and development of membrane processes using process simulation tools and explored the scale-up of membrane processes with numerous pilot plant case studies in collaboration with the chemical industry.…”
Section: Introduction 1early Historic Backgroundmentioning
confidence: 99%